Volume 3: Design and Manufacturing, Parts a and B 2010
DOI: 10.1115/imece2010-37306
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations for Characterization and Analysis of Rake Face of the WC-Co Inserts Using Taguchi Method

Abstract: In order to improve the performance of the cutting tool, it is required to model the metal cutting process at the system level. To predict and enhance the cutting tool performance the primary requirement of the system is the efficiency of the model explaining the interactions at the tool chip interface. The predominating parameters which influence the development of the system are work piece material and machining variables or sometimes both. Further the development of low cost methodology to study the chip to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Digital image showing chipping of nose under one of the medium machining conditions (M(12,23)—speed: 180 m/min, feed: 0.045 mm/rev and depth of cut: 1.5 mm). 19 …”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Digital image showing chipping of nose under one of the medium machining conditions (M(12,23)—speed: 180 m/min, feed: 0.045 mm/rev and depth of cut: 1.5 mm). 19 …”
Section: Experimental Methodologymentioning
confidence: 99%
“…(a) Consolidated chip flow path and (b) cutting tool template showing location of hard and soft coatings. 19 …”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…2. (Prasad et al,2010) identified chip flow path by conducting various machining conditions on plain Tungsten carbide inserts. It was suggested to plan for alternate hard and soft nanocoatings as per the identified zones.…”
Section: Grooves Design On Wc Cutting Toolsmentioning
confidence: 99%